The use of the time‒resolved X‒ray solution scattering for studies of globular proteins. Issue 3 (2002) - Kuwajima Kuwajima, Kunihiro Kunihiro; Arai Arai, Munehito Munehito; Inobe Inobe, Tomonao Tomonao; Ito Ito, Kazuki Kazuki; Nakao Nakao, Masaharu Masaharu; Maki Maki, Kosuke Kosuke; Kamagata Kamagata, Kiyoto Kiyoto; Kihara Kihara, Hiroshi Hiroshi; Amemiya Amemiya, Yoshiyuki Yoshiyuki
Abstract : In order to improve the low signal‒to‒noise ratio of the time‒resolved small‒angle X‒ray scattering, we have used a two‒dimensional X‒ray detector with a beryllium‒windowed X‒ray image intensifier and a charge‒coupled device as an image sensor, and applied this to studies on (1) the kinetic folding reaction of α‒lactalbumin, which accumulates the molten globule‒like intermediate at an early stage of refolding and (2) the cooperative conformational transition of Escherichia coli chaperonin GroEL induced by ATP, which occurs in an allosteric manner between the close and open conformational states. In the α‒lactalbumin reaction, we have firmly established the equivalence between the kinetic intermediate and the equilibrium molten globule state, and obtained further information about dehydration from the highly hydrated folding intermediate during a late stage of refolding. In the chaperonin study, we have successfully observed the kinetics of the allosteric transition of GroEL that occurs with a rate constant of about 3–4 s −1 at 5 ° C. The combination of the time‒resolved X‒ray scattering with other spectroscopic techniques such as circular dichroism and intrinsic fluorescence is thus very effective in understanding the conformational transitions of proteins and protein complexes.